(untitled) (Research, Society and Development, 2020)
The aquaculture and ornamental fish market is gaining a prominent role in the scenario of agribusiness in Brazil and worldwide, causing it to grow a search for professional development in this area by veterinarians. Thus, this study sought, through an investigation by means of literature review, exploring the theme of surgery in fish, with the goal of promoting a survey of major surgical procedures performed in these animals. Justifies the importance of this study for the current need for surgical procedures in certain fish due to its high economic value and sentimental, and the rarity of some ornamentals and exotic. Despite the limited availability of research material, it was possible in this study to gather important information about the procedures of surgeries in fish, this being found to be an area of veterinary medicine that still needs expansion, through research, publications and technical improvement, because there are still many gaps to be filled.